Locked out felon disenfranchisement and American democracy - Manza, Jeff.; Uggen, Christopher (Oxford : Oxford University Press, 2006)
The authors expose felon disenfranchisement as one of the most important, yet little known, threats to the health of American democracy. Their book reveals the centrality of racial factors in the origins of these laws, and their impact on politics election outcomes, and public policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ex-convicts -- Suffrage -- United States; Political rights, Loss of -- United States; Punishment -- United States